Forest Fire Detector and Fire Fighting Monitoring System Using Solar Cell Based Internet of Things (IoT) - Raden Jasa Kusumo Haryo; Budi Artono; Hanifah Nur Kumala Ningrum; Kumala Mahda Habsari; Isnani Mila Rahma (Telematika, 2022)
Forest and land fires in Indonesia, based on National Board for Disaster Management (BNPB) are recorded that the burned area reached 328,724 hectares with 2,719 hotspots in the January – August 2019 period. The factors causing forest fires include climate change, human activities in forest areas, and forest officers that can’t be monitored in real-time. The internet of things (IoT) based solar cell-based forest fire detection using for a monitoring system in real-time. This research uses PV (Photovoltaic) as power on the system. This IoT is integrated with the android application so that the user can monitor forest conditions at any time. This research uses ESP8266 12 – F as an IoT module, Arduino Uno for controlling the device, and relays. This result data are based on laboratorium test. The result of this research is a monitoring system that can monitor smoke (MQ-2 sensor), temperature and humidity (DHT22 sensor), water pressure (pressure transmitter), current and voltage in the battery charging remotely and can be controlled automatically when the sensor detects the flame.